REVIEW OF SCHEDULING SEQUENCE AND NETWORK ANALYSIS FOR PRODUCTION SYSTEM - Saravana kumar, R.; Mohan, D. Chandra (International Journal of Psychosocial Rehabilitation, 2020)
Production sequencing or scheduling is the planning of production keeping in view various constraints at the organization level. Marketing department of any organization may book the orders, competing against others, but its ultimate production and delivery largely depends on the production or operation department. Sequencing or scheduling of production is done in a way, so that overall interests of every stakeholder (like, customers, suppliers, shareholders or the owners, etc.,) are safeguard. To take an example with the same production facility, a company may cater to varied customer’s needs. When orders are booked by the marketing department, they desire to execute the orders one by one; the production department, however, needs to consider more holistically, keeping in view the machine interchangeability time, processing time, etc. For production schedule, various tools are used. In this paper, we have discussed about all such tools and methodologies.